Sraffa and Leontief revisited mathematical methods and models of a circular economy - Emmenegger, Jean-François (Walter de Gruyter GmbH, 2020)
This work is dedicated to Wassiliy Leontief's concepts of Input-Output Analysis and to the algebraic properties of Piero Sraffa's seminal models described consequently by matrix algebra and the Perron-Frobenius Theorem. Detailed examples and visualizing graphs are presented for applications of various mathematical methods.